THE LEADER OF THE SOCIALIST-REVOLUTIONARIES. RETURN FROM OBLIVION - BORIS ALEKSEEVICH Myasoyedov (Мир новой экономики, 2018)
Thanks to rehabilitation and clarification of reputation of people of science, culture, policy the original image of Russia is restored. Prophetic words of A. Vertinsky come true: "They will have a homeland".Today it is important to look for in works of scientists, officials, heads how they formulated programs and reforms.It is important to enrich the country with knowledge of those who bore the high Russian changing culture in life. Today, at last, books and articles of the best minds of Russia became available. One and a half years from number are presented to attention of readers of the World of New Economy magazine to number biographies of those who the works created economic science in Russia.In articles about Pervushin, Chuprov, Chetverikov, Chayanov, Bogdanov the author tries to draw attention to their persons and works, their place in the history of Russia.The next story - about Victor Mikhaylovich Chernov, the professional revolutionary, the leader of Social Revolutionaries and the author of the agrarian program.